The role of the modern contract law in the purview of consumer protection / Sheela Jayabalan and Daleleer Kaur Randawar - Jayabalan, Sheela; Randawar, Daleleer Kaur (Universiti Teknologi MARA, Perlis, 2017)
Consumer welfarism especially has created an impact in the sustainability of the law. Contract law becomes a significant feature to be discussed because the law of contract is the foundation on which commercial law rests. Both consumers and businesses rely on contract law to resolve disputes in business transactions. The status of laissez faire of the 17th century developed contract law based on freedom of contract. Since contracting parties have the freedom to impose obligations, rights and liabilities, they were presumed to have protected themselves from any shortcomings. The freedom of contract however was deemed insufficient to protect consumers. Social realism namely consumer welfarism became imminent to achieve contractual justice. Courts had to use equity as a tool to remedy injustices of the consumer society. Even though equity is in hand to apprehend unfairness or injustice, consumer welfarism necessitates the need to legislate the equitable principles especially for the sustainability of consumer protection. Therefore, there is call world over for contract law to be modified by legislation to afford greater protection to consumers because of consumer behaviourism. Adapting doctrinal analysis, this article discusses how consumer behaviourism has influenced the transition of the traditional law of contract to that of modern law of contract where the core value of the law is concerned about consumers' vulnerability to unjustifiable domination, the equivalence of exchange and the need to ensure co-operation. Consumer behaviourism eviscerates the formalism role of contract law and integrates contractual justice for the benefit of the community.